A Combined Association Mapping and Linkage Analysis of Kernel Number Per Spike in Common Wheat (Triticum aestivum L.) - Shi, Weiping; Hao, Chenyang; Zhang, Yong; Cheng, Jingye; Zhang, Zheng; Liu, Jian; Yi, Xin; Cheng, Xiaoming; Sun, Daizhen; Xu, Yanhao; Zhang, Xueyong; Cheng, Shunhe; et al. (Frontiers in Plant Science, 2017)
Kernel number per spike (KNPS) in wheat is a key factor that limits yield improvement. In this study, we genotyped a set of 264 cultivars, and a RIL population derived from the cross Yangmai 13/C615 using the 90 K wheat iSelect SNP array. We detected 62 significantly associated signals for KNPS at 47 single nucleotide polymorphism (SNP) loci through genome-wide association analysis of data obtained from multiple environments. These loci were on 19 chromosomes, and the phenotypic variation attributable to each one ranged from 1.53 to 39.52%. Twelve (25.53%) of the loci were also significantly associated with KNPS in the RIL population grown in multiple environments. For example, BS00022896_51-2ATT, BobWhite_c10539_201-2DAA, Excalibur_c73633_120-3BGG, and Kukri_c35508_426-7DTT were significantly associated with KNPS in all environments. Our findings demonstrate the effective integration of association mapping and linkage analysis for KNPS, and underpin KNPS as a target trait for marker-assisted selection and genetic fine mapping.